Contemporary ethical problem - Euthanasia - Ręba, Patrycja (Journal of Education, Health and Sport, 2019)
Admission Cultural changes and more dynamic medical techniques result in a multitude of questions related to the bioethical aspects of medicine. In recent years, increased interest in the sphere of death. One of the issues related to the process of dying euthanasia, which raises many philosophical controversies in many environments including among lawyers, doctors, philosophers and ethicists. Permanent ongoing disputes about whether terminally ill person, with the right to a dignified life and a decent death, may request to shorten their suffering. Etymologically the term comes from the Greek,euthanatos This juxtaposition of two words: eu - good and thanatos - death, which means "good death" or "death gentle and free of suffering." In historical perspective, euthanasia has always been present in the history of mankind, although this term hid multiple definitions and practical applications. In modern times, euthanasia is to terminate the patient’s life. Aim The aim of the study is to analyze phenomenon euthanasia in terms of ethical and medical. Material and methods A review of available literature. Results Despite extensive discussion blurred the differences between the resignation of persistent therapy, active and passive euthanasia - but you can not erase the difference between natural death and intentional, and imposed due. In the strict sense of euthanasia we have to do when the so-called dignified death wants to achieve by some form of suicide or homicide. The purpose of medicine is not a fight to the death, but the health and care of the sick. Palliative medicine and hospice care should be more appreciated and used. They are just as important as the medical staff and are closest to the patient in the most difficult and the most important moment of his life, at the time of his death. This existential attempt to humanity of every person is important not only for the patient but for thehis family, for the environment, for the community, for the whole culture. Conclusions Euthanasia is an extremely complex problem. It is difficult to define clear limits, which would distinguish her way clear of other activities in the field of medicine. Each case is separate and must be adapted to it all "for" and "against."Analyzing the arguments for and against euthanasia is not easy to take a clear position. You can not make generalizations, responsible for suffering, Terminally ill family that daily struggle with unimaginable suffering coming. It is easy to criticize escape from suffering when you yourself were not in such a situation. However it is a very cautious approach to the legalization of euthanasia, because even partial leave by law, may be the reason for abuse. There is a risk that the boundary between murder and euthanasia may be fluid.It calms the public saying that it was for the good of the patient, that everyone has the right to a dignified death, it was at the request of the patient. The disadvantage of humanistic ethics argument is that she sees the man as an ordinary part of the world, which favors the objectification of subjectivity, which we are entitled.